Determinasi Indikator Ekonomi dan Pembangunan Terhadap Pengangguran di ASEAN6: Analisis Data Panel - Jeniko, Fiona; Trihadmini, Nuning (PPJP ULM, 2025)
This study investigates the determinants of unemployment in six ASEAN countries—Indonesia, Malaysia, the Philippines, Singapore, Thailand, and Vietnam—during the 2010–2023 period, focusing on the roles of Foreign Direct Investment (FDI), Human Development Index (HDI), Gross Domestic Product (GDP), Consumer Price Index (CPI), and the Covid-19 pandemic. Using panel data analysis with a fixed effects model, the results show that FDI has no significant impact on unemployment, while HDI unexpectedly has a positive correlation. GDP significantly reduces unemployment, confirming the role of economic growth in absorbing labor. CPI, contrary to conventional theory, also significantly lowers unemployment. The Covid-19 pandemic, however, significantly increases unemployment across the region. These findings highlight the complex interplay between macroeconomic indicators and labor markets in ASEAN6 and suggest the need for targeted policy responses that address structural vulnerabilities and enhance labor market resilience.